2019
DOI: 10.1186/s12906-019-2535-3
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-inflammatory effect of naringin and sericin combination on human peripheral blood mononuclear cells (hPBMCs) from patient with psoriasis

Abstract: Background Several immunological pathways, particularly skin inflammation via various pro-inflammatory cytokines have been reported to be involved in the pathogenesis and clinical manifestations of psoriasis. The aim of the study was to investigate the potential role of naringin from Citrus maxima (Burm.) Merr and sericin from Bombyx mori combination in the treatment of psoriasis. Inhibitory effects on the expression of mRNA and the production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Naringin shows a productive anti-inflammatory activity, as reported in the present and previous studies [129][130][131]. This flavanone glycoside can also constrain the expression of the pro-inflammatory cytokines, including IL-1β and IL-6.…”
Section: Naringinsupporting
confidence: 87%
“…Naringin shows a productive anti-inflammatory activity, as reported in the present and previous studies [129][130][131]. This flavanone glycoside can also constrain the expression of the pro-inflammatory cytokines, including IL-1β and IL-6.…”
Section: Naringinsupporting
confidence: 87%
“…Naringin, a major flavanone of grapefruit and other citrus fruits, demonstrates several beneficial properties, including antioxidant and anticancer activities [ 152 , 153 , 154 , 155 ]. Naringin inhibited glucose metabolism in A375 melanoma cells in a concentration-dependent manner.…”
Section: Beneficial Effects Of Flavonoids In the Regulation Of Hypmentioning
confidence: 99%
“… 30 , 31 Accumulating evidence suggests that naringin possesses a variety of pharmacological activities, including anti-osteoporotic, anti-cancer, anti-apoptotic, and anti-inflammatory effects, as well as effects on metabolic syndrome and central nervous system diseases, including neurological disorders. 32 , 33 , 34 Several reports have confirmed that naringin protects against steroid-induced ischemic necrosis by upregulating PPARγ, 35 and naringin can activate the 5’ adenosine monophosphate-activated protein kinase (AMPK) pathway to induce anti-inflammatory activity in sepsis. 36 Our previous studies have confirmed that naringin improves sepsis-induced intestinal injury through the regulation of the ROCK1/2 pathway, but the study of macrophage polarization by naringin has not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%